Understanding kidney injury in COVID-19; a pressing priority - Elham Ahmadipour; Bhaskar VKS Lakkakula; Golnaz Vahdani; Ramin Tolouian; Hedieh Ragati Haghi; Doris Delgado; Luiz Augusto Fernandes da Silva; Masoud Hafizi (Society of Diabetic Nephropathy Prevention, 2021)
The 2019 novel coronavirus disease (COVID-19) is a newly defined infectious and highly contagious acute disease caused by the severe acute respiratory syndrome coronavirus 2 ( (SARS-CoV-2). COVID-19 is mainly characterized by an acute respiratory disease however it can also affect multiple other organ systems such as the kidney, gastrointestinal tract, heart, vascular system, and the central nervous system. Kidney involvement is frequent in patients with COVID-19 and this review aims to explore the available data on kidney and COVID-19. In conclusion, COVID-19 infection can affect renal function and may cause acute kidney injury (AKI), due to several mechanisms that need to be fully elucidated. As only supportive management strategies are available for treating AKI in COVID-19, it is necessary to identify and preserve renal function during SARS-CoV-2 infection.